2022
DOI: 10.5796/electrochemistry.22-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phase Change and Cu Doping on the Li Storage Properties of Rutile TiO<sub>2</sub>

Abstract: The crystal structure and Li storage properties of Cu-doped rutile TiO2 after a phase change caused by lithiation were investigated for the first time. Structural analysis results confirmed that undoped rutile TiO2 was transformed to a disordered layered rock-salt LixTiO2 structure with a small volume expansion of only 1 % when cycled in a potential range of 1.0−3.0 V vs. Li + /Li. A substitutional solid solution of Cu 2+ was formed in layered LixTiO2. The Cu doping increased both the interlayer distance and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…We have recently developed rutile-type TiO 2 as high-performance anode materials for Li-ion batteries and Na-ion batteries using liquid electrolytes. In particular, it has been revealed that the impurity element doping into TiO 2 could remarkably enhance the anode performances. We confirmed that doping has mainly two important effects: the enhancement in electronic conductivity and the expansion of the Li-ion diffusion path. It is expected that the material strategy of the impurity-doped TiO 2 anodes will be useful not only for liquid-type batteries but also for solid-type batteries.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…We have recently developed rutile-type TiO 2 as high-performance anode materials for Li-ion batteries and Na-ion batteries using liquid electrolytes. In particular, it has been revealed that the impurity element doping into TiO 2 could remarkably enhance the anode performances. We confirmed that doping has mainly two important effects: the enhancement in electronic conductivity and the expansion of the Li-ion diffusion path. It is expected that the material strategy of the impurity-doped TiO 2 anodes will be useful not only for liquid-type batteries but also for solid-type batteries.…”
Section: Introductionsupporting
confidence: 54%
“…In the initial charge curves, there are two potential plateaus at around 1.5 and 1.2 V vs Li + /Li. In the recent studies containing our works, the charge–discharge reaction mechanism of rutile TiO 2 electrodes has been clarified. , The first plateau at 1.5 V can be ascribed to a reversible phase change of rutile TiO 2 ( P 4 2 / mnm ) to monoclinic distorted rutile Li x TiO 2 ( P 2/ m ). The second plateau at 1.2 V can be attributed to an irreversible phase change from the distorted rutile Li x TiO 2 to monoclinic distorted Li x TiO 2 ( P 2/ m ) with a layered rock-salt structure (α-NaFeO 2 -type).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations